Plasmodium falciparum Infection Does Not Affect Human Immunodeficiency Virus Viral Load in Coinfected Rwandan Adults. (21st August 2014) - Subramaniam, Krishanthi; Plank, Rebeca M.; Lin, Nina; Goldman-Yassen, Adam; Ivan, Emil; Becerril, Carlos; Kemal, Kimdar; Heo, Moonseong; Keller, Marla J.; Mutimura, Eugene; Anastos, Kathryn; Daily, Johanna P.
Abstract : In contrast to prior studies, mild malaria infection had no impact on HIV Viral Loads(VL) in Rwanda. Over fifty percent of patients prescribed ARV had detectable VL; 25% had genotypic resistance. Eleven percent of patients with mild malaria were newly diagnosed with HIV. Abstract: Background. Plasmodium falciparum infection has been reported to increase human immunodeficiency virus (HIV) viral load (VL), which can facilitate HIV transmission. We prospectively studied the impact of mild P falciparum coinfection on HIV VL in Rwanda. Methods. We measured plasma HIV VL at presentation with malaria infection and weekly for 4 weeks after artemether-lumefantrine treatment in Rwandan adults infected with HIV with P falciparum malaria. Regression analyses were used to examine associations between malaria infection and HIV VL changes. Samples with detectable virus underwent genotypic drug-resistance testing. Results. We enrolled 28 HIV-malaria coinfected patients and observed 27 of them for 5 weeks. Three patients (11%) were newly diagnosed with HIV. Acute P falciparum infection had no significant effect on HIV VL slope over 28 days of follow-up. Ten patients with VL <40 copies/mL at enrollment maintained viral suppression throughout. Seventeen patients had a detectable VL at enrollment including 9 (53%) who reported 100% adherence to ARVs; 3 of these had detectable genotypic drug resistance. Conclusions. Unlike studies from highly malaria-endemic areas, we did not identify an effect of P falciparum infection on HIV VL; therefore, malaria is not likely to increase HIV-transmission risk in our setting. However, routine HIV testing should be offered to adults presenting with acute malaria in Rwanda. Most importantly, we identified a large percentage of patients with detectable HIV VL despite antiretroviral (ARV) therapy. Some of these patients had HIV genotypic drug resistance. Larger studies are needed to define the prevalence and factors associated with detectable HIV VL in patients prescribed ARVs in Rwanda.